EPISTEMOLOGI BAYANI, BURHANI DAN IRFANI DALAM MEMPEROLEH PENGETAHUAN TENTANG MASHLAHAH - Makiah, Zulpa (Universitas Islam Negeri Antasari Banjarmasin, 2014)
Mashlahah or concept of the benefits an essential part of Islamic law. Ulama (muslim scholar) have various statements about mashlahah. In one statement, mashlahah is nash authorities that people have to understand exclusively and strictly. In another, Ulama ensure that intelligence has a role to decisive the benefit. There are three way to gain knowledge about mashlahah, namely bayani, burhani, and irfani. Nash is believed to be esoteric and exoteric, but the meaning of esoteric is more dominant. This paper wants to explore how to gain knowledge about mashlahah in bayani, burhani, and irfani perspective.